THE EFFECT OF MASS FLOW RATE ON THE HEAT TRANSFER SOLAR WATER HEATER WITH USING NANO FLUID ON CFD - Singh, Gyan; Tembhurne, Yogesh; Pandey, Vijaykant (Innovative Research Thoughts, 2018)
This study was performed in an open environment in bright sunlight. The solar water heater was used for the study of the effect of sunlight on the Nano-fluids. The solar water heater was directly facing the sun. A Nano-fluid was prepared by using Nano-particles of different materials with water. The mass flow rate of the water at the inlet was 1lpm (0.017kg/s). The Nano-fluids were made to flow through the solar heater from the inlet at a temperature of about 320k. The outlet temperature of the Nano-fluid was observed in order to find the Nano-fluid with the highest temperature. The results shows to increase the efficiency and performance of solar heat pipe collector using PbO nanofluids at 0.5% fraction.